Izviren kombiniran večfazni model mešalne faze eksplozije pare - Leskovar, Matjaž (Strojniški vestnik, 2002)
In multiphase flow, different distributions can occur that cannot be adequately modeled with just free-surface models or with just multiphase models. Such a distribution of phases occurs for example, in isothermal steam-explosion premixing experiments, where dispersed spheres penetrate the water and the water-air surface remains sharp. A common practice when modeling isothermal premixing experiments is to treat all three phases involved - the water, the air and the spheres phase - equally, with multiphase flow models. In this way the water-air surface is treated as a dispersed flow of bubbles in water or droplets in air, which is a physically incorrect picture and because of very strong momentum-coupling terms also numerically not an easily solvable problem. Therefore, we decided to develop an original, combined multiphase model, where the spheres are treated, as is usual with a multiphase flow model, whereas the water-air surface is treated with a free-surface model. ...
Keywords: tok večfazni; modeli večfazni; eksplozije pare; metode z novojsko funkcijo; simuliranje; večfazni tok; modeliranje; para; eksplozije; simulacije